English Teacher’s Perceptions of The Change in Curriculum to an Independent Curriculum - Henti Sartikasari Gulo (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The curriculum is part of a learning management system that involves planning the implementation of learning and becomes a guideline and guide for teachers in carrying out learning activities. The purpose of this research is to find out the teacher's perception of curriculum changes in Indonesia, especially for English teachers. In this research, the method used is descriptive qualitative research method and the data obtained is from the results of interviews. The results of the study show that the opinions of the teachers reflect diverse views regarding curriculum changes in Indonesia. Some considered it to have a positive impact, such as an increased focus on attitudes and skills, as well as enhancing students' creativity. However, others noted negative impacts such as students' adaptation difficulties and new problems arising, including a lack of support from some students and the learning environment for the government standards.